Intensification of catalytic CO2 methanation mediated by in-situ water removal through a high-temperature polymeric thin-film composite membrane. (January 2022) - Escorihuela, Sara; Cerdá-Moreno, Cristina; Weigelt, Fynn; Remiro-Buenamañana, Sonia; Escolástico, Sonia; Tena, Alberto; Shishatskiy, Sergey; Brinkmann, Torsten; Chica, Antonio; Serra, Jose M.
Graphical abstract: Highlights: H2 O removal through polyimide 6FDA-6FpDA membrane carried out at 260 °C. In-situ H2 O extraction enabled intensifying methanation reaction. H2 O removal of 12.5 % from and specific H2 O flux of ∼100 g·h −1 m −2 were reached. CO2 conversion stability was greatly improved in the catalytic membrane reactor. Abstract: Catalytic CO2 methanation technology can be improved by process intensification, i.e. enabling higher energy efficiency and process sustainability. Here, thin-film composite membranes (TFCM) were developed for in-situ water removal in a catalytic membrane reactor (CMR) for the Sabatier process. The selective separation layer (1.4 μm-thick) of the composite membrane is made of the polyimide 6FDA-6FpDA, a glassy polyimide, which exhibits high permeability and selectivity together with stable function at unprecedented high temperatures (>200 °C), compared to polyimides reported until now (90 °C), thus matching the temperature range of Sabatier reactors. Remarkably, TFCM developed in this work, allow to extract an outstanding amount of water up to 1 m 3 /(m 2 ·h·bar) at 260 °C. TFCM was implemented for the water removal from the methanation reaction in a CMR operated at 260 °C and using Ni-Todorokite as catalyst. The TFCM-mediated water-extraction enabled to raise both catalytic stability and activity during CMR operation. CO2 conversion stability was greatly improved exhibiting a conversion value of 72 % during the course of the reaction (21 % increase in CO2 conversion), with a water removal of 12.5 % and specific flux of ∼100 g·h −1 m −2 .